Math, asked by pranatipanda12345, 1 year ago

the solution of the equation 3/4 ( n-1) = n-3 is


hafeezhtech: do you know hindi
pranatipanda12345: yes...
pranatipanda12345: u???
hafeezhtech: yep i do know hindi
pranatipanda12345: great...but i am not in touch ..
pranatipanda12345: hannam???
pranatipanda12345: are u muslim???
pranatipanda12345: ok bye...have a great day ahead .....but plz follow me na
pranatipanda12345: goood night
hafeezhtech: bye

Answers

Answered by hafeezhtech
1

Hello

3/4(n-1) = n- 3

3(n-1)/4 = n - 3

3n - 3/4 = n-3

3n-3 = 4(n-3)

3n - 3 = 4n -12

4n - 3n = 12- 3

n = 9

in your 2nd question

Gagan is thinking of a number .when he divided by 3 and then adds 4, the answer is half of the number .find the number

Let the number be x

given in the question

x divided by 3 +4 = half the number

x/3+4 = x/2

now,

x + 4*3/3 = x/2 (we took common in the denominator)

x+12/3= x/2

x+12 = 3*x/2 (we sent the 3 in the denominator to the numerator of the other side)

x+12 = 3x /2

(x +12)*2 = 3x (we sent the 2 in the denominator to the other side)

2x +24 = 3x

24 = 3x-2x

24= x

x= 24


pranatipanda12345: in my math book ....
hafeezhtech: which ncert
pranatipanda12345: core composite mathematics..
pranatipanda12345: are u class 7?
hafeezhtech: yes i am in 7 this is my brother account
hafeezhtech: my account is Hannanm
hafeezhtech: bye gn
pranatipanda12345: bye...
hafeezhtech: :)
pranatipanda12345: ^_^
Answered by Anonymous
2

\huge \red { \boxed{ \boxed{ \mathsf{ \mid \ulcorner Answer :-\urcorner \mid }}}}

Given :-

 \bf{ \frac{3(n - 1)}{4}  = n - 3}

Let this be equation 1.

To Find :-

Value of n.

Solution :-

 \sf{ \frac{3(n - 1)}{4} = n - 3 } \\  \\  \sf  \implies{ \frac{3n - 3}{4} = n - 3 }

By cross multiplication

\sf  \implies{3n - 3 = 4(n - 3)} \\  \\  \sf  \implies{3n - 3 = 4n - 12} \\  \\  \sf  \implies{3n - 4n =  - 12 + 3} \\  \\  \sf  \implies{ - n =  - 9} \\  \\  \sf  \implies{  \cancel- n = \cancel  - 9}

\huge{\boxed{\blue{\sf{n = 9}}}}

\rule{200}{2}

Verification :-

Put value of n in equation 1.

\sf{\frac{3(9-1)}{4} = 9 - 3}

\implies{\sf{\frac{\cancel24}{\cancel4} = 6}}

\sf{\implies{6 = 6}}

L. H. S = R. H. S

Hence, verified

Similar questions